Anonymous vehicle authentication scheme based on blockchain technology in the intersection scenario - Hao WANG; Tianhao WU; Konglin ZHU; Lin ZHANG (网络与信息安全学报)
With the development of intelligent transportation system,the vehicles will no longer be controlled by the traditional traffic light when they enter or leave the intersection.Instead,they will interact with the local server (LS) near the intersection and accept the regulation of LS.The basic of the security vehicle communication at intersections is authentication of network node.Based on this,an anonymous vehicle authentication scheme based on blockchain technology was proposed.The scheme employed a hybrid cryptography based on identity and hash message authentication code,and recorded the authentication results in blockchains.According to simulation testing and result analysis,the scheme ensures the anonymity and privacy-preserving,with less communication overhead compared to other methods.